Polysaccharides from Ganoderma Sinense - rice bran fermentation products and their anti-tumor activities on non-small-cell lung cancer - Wei Han; Hongjuan Chen; Lin Zhou; Haijie Zou; Xiaohong Luo; Bo Sun; Xuhui Zhuang (BMC, 2021)
Abstract Background Non-small-cell lung cancer (NSCLC) accounts more than 80% of the lung cancer cases. Polysaccharides in rice bran and its fermentation products have been proven to suppress many cancers. However, the report on inhibiting NSCLC is few. In this paper, the polysaccharides with suppression activity to H1299 NSCLC in the fermentation products of full-fat rice bran and defatted rice bran were studied in vitro and in vivo. Method Polysaccharides (GSRBPs) were extracted from Ganoderma sinense - full-fat rice bran (GS-FRB) and Ganoderma sinense - defatted rice bran (GS-DRB) fermentation products. The structure information of the GSRBPs was studied using HPLC analysis. The anti-tumor activities on H1299 NSCLC of GSRBPs in vitro study was performed using MTT method. The in vivo studies use BALB/c-nu nude mice as H1299 NSCLC bearing mice. Result All the polysaccharides contained two fractions, GSFPS-1 and GSFPS-2. The molecular weight and the ratio of GSFPS-1 and GSFPS-2 were different in GS-FRB and GS-DRB. At the earlier state of fermentation, all polysaccharides were composed of D-glu, D-man, D-xyl and L-ara with certain molar ratios. But at the latter stage, polysaccharides in GS-FRB were composed of D-glu, D-man, D-xyl, L-ara and D-fru, while these in GS-DRB only composed of D-glu and D-man. In the in vitro study, the IC50 of RBS and GSRBPs was as GS-DRB-11 (40.62 μg/mL), GS-FRB-9 (43.82 μg/mL), GS-DRB-7 (48.08 μg/mL), RBS (49.56 μg/mL), GS-DRB-9 (49.91 μg/mL), GS-DRB-13 (51.89 μg/mL), GS-FRB-11 (53.75 μg/mL), GS-FRB-7 (56.84 μg/mL), GS-DRB-13 (60.63 μg/mL) from small to large. In the in vivo study, the H1299 NSCLC inhibition rate (InRa) of RBS and GSRBPs were GS-DRB-11 (86.81%) > GS-DRB-9 (86.01%) > GS-FRB-9 (84.88%) > GS-DRB-7 (82.21%) > GS-DRB-13 (78.04%) > RBS (76.06%) > GS-FRB-13 (65.44%) > GS-FRB-11 (64.70%) > GS-FRB-7 (27.87%). The GSFPS-2 area percent was negatively correlated to the IC50 and was positively correlated to the InRa. This means the GSFPS-2 had much higher anti-tumor activity than GSFPS-1. Conclusion GSFPS-2 had higher anti-tumor activities, and the lipid in the rice bran has a decisive effect on the structures of polysaccharides produced by fermentation. Therefore, GSRBPs could be considered as potential novel agents to suppress H1299 non-small-cell lung cancer.